Dietary Feed Additive Microencapsulation Synbiotic on Physical Quality of Broiler Chicken Meat - Ningsih, Niati; Yulinarsari, Alditya P.; Muhamad, Nur; Poernomo, Hadi (Syiah Kuala University, 2025)
This research aimed to investigate the microencapsulation of synbiotics that combine probiotics, Bacillus subtilis, with prebiotic MOS for poultry diet to influence the physical quality of poultry meat. The material used in this study was 100 one-day-old unsexed broilers Cobb 500. The birds were randomly divided into the following 4 experimental groups, with five replications: The treatments were (T1) basal diet (control) without microencapsulation Synbiotic, T2, T3, and T4 supplementation basal diet with 0.25, 0.50, and 0.75% of microencapsulation synbiotics of Bacillus subtilis and MOS, respectively. The variables were physical qualities of poultry meat, including acidity (pH), cooking losses, water holding capacity (WHC), and hardness. The basal diet was formulated to meet completely the nutrient requirements broilers based on NRC (1994) recommendations. The dietary treatments were based on corn grain-soybean meal and balanced with other nutrients. The data were analyzed with one-way ANOVA in a Completely Randomized Design (CRD) using the Statistical Package for Social Science or IBM SPSS Statistics version 26, significant differences among the means were determined by using Duncans multiple range test at P0.05. The results showed that the treatment groups did not have a significant effect (P value0.05) on the physical qualities of broiler meat, which are acidity (pH), cooking losses, water holding capacity (WHC), and tenderness. To conclude, supplementation of microencapsulation synbiotic has no negative effects on the physical qualities of the meat reflected in the value of all variables, which are in the normal range of the physical quality of broiler meat.